Rural education a reality: a teacher's life story and her work in rural areas (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2019)
Rural education has enabled many teachers to grow, not only because they fulfill their duties, but also because they encounter each life story that makes their work more meaningful. Given the above, this article aims to analyze rural education from a realistic perspective, based on the life story of a teacher and her rural work experience. It takes a qualitative approach, using an ethnographic method and reflective research based on the story of a rural education teacher, her experiences, and her life lessons.